Strategies to enhanced production of biomass and natural antioxidants of Cichorium intybus L. hairy roots by using nanoparticle elicitors - Nga, Mai Thi Phuong; Linh, Tang Khanh; Tra, Nguyen Pham Cam; Linh, Huynh Thi Phuong (Vietnam Journal of Biotechnology, 2024)
This study describes the influence of silver nanoparticles (AgNPs) and selenium nanoparticles (SeNPs) on the biomass and phytochemical production in the hairy root (HR) cultures of Cichorium intybus L. The HRs were grown in ½ Murashige and Skoog (MS) medium supplemented with sucrose (30 g/L) and AgNPs or SeNPs at two selected concentrations for 25 days on the shaker at 110 rpm in the dark. The results showed that SeNPs stimulated HR growth whereas AgNPs inhibited it at both concentrations used. Peroxidase activity was higher than catalase activity. In most cases, the antioxidant enzyme activities were significantly higher in the HRs elicited by elicitors than in control HRs. The activities of catalase and peroxidase reached their highest levels at approximately 16.7 and 486.4 u/mg protein, respectively. DPPH radical scavenging activity was highest in the HRs elicited by AgNPs. AgNPs (3.25 and 1.5625 mg/L) elicited HR extracts had significantly enhanced the production of total phenolic, and total flavonoid contents compared to the control HR extracts. The maximum total phenolic content was 87.04 ± 6.23 mg/g gallic equivalent, and it was 139.03 ± 3.56 mg/g ascorbic acid equivalent in total flavonoid content in the HRs elicited by AgNPs. The HRs elicited by SeNPs produce an average amount of total phenolic, flavonoid, and DPPH radical scavenging activity which were also significantly higher than those produced by control HRs. The results from our study suggested the effectiveness of the elicitation process in enhancing the root biomass, total phenolic, and flavonoid content. NPs-elicited Chicory HRs offered an effective and favorable in vitro method to improve the production of bioactive compounds for potential uses in pharmaceutical industries.